Studying and suggesting several contents to institutionalise the management of remote sensing activities in Vietnam based on the legal basis and practical requirements - Thi Phuong Thao Vu; Quoc Hung Le (Vietnam Journal of Science, Technology and Engineering)
In Vietnam, achievements in research and application of remote sensing technology have significantly improved the efficiency of many socio-economic activities. Although the application and development of this technology are underway, numerous inadequacies have been revealed. The lack of a comprehensive remote sensing law in Vietnam to address and support socio-economic activities has become evident, leading to many difficulties in assessing the quality of remote sensing products of different agencies, making it challenging to develop remote sensing applications and services. Furthermore, remote sensing application agencies are mainly concentrated in central agencies, while remote sensing in localities has high practical significance and is essential to serve the state management of natural resources and the environment locally. In addition, there is no close coordination between local agencies and central agencies - the main reason for overlapping work contents, causing a waste of budget investment and, at the same time, leading to confusion and passivity in arranging annual plans and allocating expenditures for remote sensing. Thus, institutionalising the management of remote sensing activities based on legal and practical requirements in Vietnam is an urgent need. This includes the management of space and ground segments, commercialisation of remote sensing, international training and cooperation, and the creation of a legal corridor to promote remote sensing development, overcome policy gaps, and support the socio-economic life, national defence, security, and environmental monitoring.